HUBUNGAN TINGKAT PENGETAHUAN MOBILISASI DINI DENGAN PERILAKU MOBILISASI DINI IBU POSTPARTUM SECTIO CAESAREA (SC) DI RUANGAN SASANDO DAN FLAMBOYAN RSUD Prof. Dr. W. Z JOHANNES KUPANG - Lusia Karolinda Lema (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
Sectio Caesarea postpartum mothers need to make early mobilization that mothers need to be equipped with enough knowledge about early mobilization if patients do not Sectio Caesarea early mobilization, it will cause an increase in body temperature, abnormal bleeding and uterine infolusi not baik.Tujuan this research is to know the correlation between knowledge of early mobilization with early mobilization behavior Postpartum mothers in room SC Flamboyan Sasando and hospitals. Prof. Dr. W.Z. Johannes Kupang. The results showed that out of 32 respondents showed 13 respondents (41%) have a level of knowledge is good, 18 respondents (56%) have a level of knowledge sufficient and 1 respondent (3%) have a level of knowledge is less, while 32 respondents showed postpartum maternal SC which has good behavior in conducting early mobilization were 9 people (28%) and had a pretty good conduct as many as 23 people (72%). Based on the analysis using Chi Square test was obtained p value = 0.090 (α = 0.05), the p> 0.05 indicates no relationship between the level of knowledge of early mobilization with early mobilization of postpartum SC behavior in space Flamboyan Sasando and hospitals. Prof. Dr. W.Z. Johannes Kupang Keywords: Knowledge Level, Early Mobilization Behavior, Mother Postpartum Sectio Caesarea